Integrated Photocatalytic and Biological Treatment of Bio-Recalcitrant Compounds in Textile Industry Effluent - Kumar, Anoop (My University, 2007)
The worst impact of rapid development in dyes and textile industries in the recent decades has resulted in the accumulation of large quantities of recalcitrant pollutants into our water cycle. Traditionally physicochemical methods used for wastewater treatment have inherent limitations in their applicability, effectiveness and cost. The biological treatment methods are ineffective because the effluents contain several organic and other recalcitrant compounds that have high aromaticity (aromatic phenols, amines, nitro etc.) and low biodegradability and these are the major environment pollutants. The combination of photocatalytic process using both homogenous and heterogeneous catalysts like Fenton’s process and TiO2 and its modified forms respectively, with biological treatment for the degradation of organic pollutants can provide a viable alternative for the detoxification and recycling of industrial wastewater. The project undertaken involves the development of degradation technique that couples solar and biological processes for the treatment of biorecalcitrant, nonbiodegradable and toxic organic substances present in the textile effluent. In this study, the optimization of the process using industry effluent (from nearby Textile industry) has been studied by varying catalyst concentration, variation of pH, addition of oxidant, and treatment under solar irradiation as pre and post treatment to the existing biological treatment for maximum degradation. The analysis of the products by measuring COD, BOD, TSS, TS, TDS, pH, Color has been done.
Keywords: Treatment of Bio-Recalcitrant Compounds; Solar Field Technology; Photocatalytic Treatment; Biological Tretment; Fenton’s Process